Computational Fluid Dynamic (CFD) Analysis of Tray Dryer Performance for Turmeric Rhizome Drying - Duc T. Le; Nhu V.P Le; Yen H.P Duong; Tan M. Le; Viet T. Tran (Chemical Engineering Transactions)
In this research, Computational Fluid Dynamics (CFD) is employed to simulate the distribution of velocity, temperature, and mass fraction of water vapor in moist air and the evaporation rate of drying material within a drying chamber. These simulations are grounded in the application of conservation principles for mass, momentum, and energy. Experiments were conducted at building H3 in HCMUT at the Di An Campus to measure velocity and temperature at various locations within the drying chamber and the mass of dried turmeric rhizome. To model the drying process of turmeric rhizome in a tray dryer, the CFD software ANSYS Fluent was utilized for 3D modeling. Various models, such as the standard k-epsilon turbulence model and the species model used in conjunction with the transient solver, were employed to analyze the distribution of velocity, temperature, the mass fraction of water vapor in moist air, and the evaporation rate of the drying material within the tray dryer over 8000 seconds with a drying agent at 50 °C. The simulation results for the evaporation rate of the drying material and drying temperatures were compared to experimental data and found to be in excellent agreement. This was indicated by R² values of 1, 0.99, and 0.97 for the three drying stages. Consequently, simulation can serve as a viable option for studying drying mechanisms and mitigating certain limitations associated with conducting experiments.